Global warming, renal function and heart failure over 20 years. (15th October 2022) - Aimo, Alberto; Lupon, Josep; Spitaleri, Giosafat; Domingo, Mar; Codina, Pau; Santiago-Vacas, Evelyn; Cediel, German; Zamora, Elizabet; Troya, Maribel; Santesmases, Javier; Romero-Gonzalez, Gregorio A.; Nunez, Julio; et al.
Abstract: Background: The impact of increasing temperatures on renal function in heart failure (HF) outpatients has never been specifically analyzed. Methods: We retrieved creatinine and estimated glomerular filtration rate (eGFR) values of all HF outpatients followed at a HF clinic and temperature data from 2002 to 2021. For each patient and each year we averaged values of creatinine, eGFR and monthly temperatures during summer and the rest of the year. Results: The study cohort included 2167 HF patients undergoing 25, 865 elective visits, with a median of 14 visits for each patient (interquartile range 7–23). At the first visit, patients (70% men) had an age of 67 ± 13 years, and a left ventricular ejection fraction of 35 ± 14%. Creatinine was 1.25 ± 0.51 mg/dL, and eGFR was 65 ± 25 mL/min/1.73 m 2 . When pooling together all average values of creatinine and eGFR measured during summer or in the rest of the year, creatinine was significantly higher in summer (difference 0.04, 95% confidence interval [CI] 0.04 to 0.05, p < 0.001), and eGFR was slightly lower (difference − 2.0, 95% CI -2.3 to −1.8, p < 0.001). Temperature rise during summer increased from 2002 to 2021. The absolute (Δ) and percent (Δ%) elevation in temperature during summer displayed independent associations with Δ and Δ% creatinine and eGFR after adjusting for age, sex, plasma creatinine, and HF therapies. Conclusions: The magnitude of temperature elevation during summer has increased over 20 years. This elevation correlates with the decline in renal function during summer. This might be an example of how global warming is affecting human health. Graphical abstract: Temperature elevation during summer and worsening renal function over a 20-year timespan The graph is a schematic representation of the changes in temperatures and renal function over time and not an accurate representation. eGFR, estimated glomerular filtration rate; HF, heart failure. Unlabelled Image Highlights: This study cohort included 2167 HF patients undergoing 25, 865 elective visits. The magnitude of temperature elevation during summer has increased over 20 years. This elevation correlates with the decline in renal function during summer.